Answer:
Answer as a decimal:
Answer as a fraction:
Explanation:
y - 15 = 3x
-2x + 5y = -3
Solve the first equation first to substitute into second equation
y - 15 = 3x
Add 15 to both sides of the equation
y = 3x + 15
Substitute this value of y into second equation
-2x + 5y = -3
2x + 5(3x + 15) = -3
Multiply
2x + 15x + 75 = -3
Add the x's
17x + 75 = -3
Subtract 75 from both sides of the equation
17x = -78
Divide both sides of the equation by 17
Answer as a decimal:
Answer as a fraction:
Hope this helps :)